DEVELOPMENT OF ENGINEERING DRAWING LEARNING MODULE FOR VOCATIONAL STUDENT AT PROPERTY CONSTRUCTION BUSINESS EXPERTISE PROGRAM - Luthfi Arfianti (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
This study aims to: (1) develop the learning media for the Technical Drawing module in the engineering drawing subject of class X Property Construction Business (BKP) at SMK Negeri 1 Percut Sei Tuan, (2) To determine the validity level of the material and media as learning media for students. This study uses the Research and Development development research method which includes the stages of identifying potentials and problems, gathering information, product design, design validation, and design improvement. The instrument used was a questionnaire. This questionnaire is used to test the feasibility of the media in the module through material validation and media validation. Based on the research results it is known that the Technical Drawing module as a learning medium for Engineering Drawing subjects refers to a curriculum consisting of 6 chapters. The results of the feasibility test for material experts with an average score of 125 are in the very good category. And the results of the feasibility test for media experts with an average score of 148 are in the very good category. The results showed that the Engineering Drawing learning module was feasible to use for class X BKP students at SMK Negeri 1 Percut Sei Tuan.